Health risks associated with radon concentrations in carbonate and evaporite sequences of the uranium-rich district Karak, Pakistan - Khan, Mumtaz Ali; Khattak, Nimat Ullah; Hanif, Muhammad; Al-Ansari, Nadhir; Khan, Muhammad Bashir; Ehsan, Muhsan; Elbeltagi, Ahmed (Frontiers in Environmental Science, 2022)
The present research was carried out to investigate the behavior of radon (222Rn) concentration over the carbonate and evaporite sequence and to assess the related health hazards. A total of 50 stations from three different stratigraphic units, namely Bahadurkhel Salt, Jatta Gypsum and Kohat Formation of Eocene age were analyzed for radon concentrations in district Karak of Khyber Pakhtunkhwa, Pakistan. Measurements for radon levels were made by using RAD7 of Durridge, USA. The highest average 222Rn concentration (88.48 pCi/l) was found in the Limestone unit of Kohat Formation of Eocene age. Whilst, the lowest radon levels were observed in the salt bearing strata of Bahadurkhel Salt of Eocene age. The study revealed that the average radon concentration in all the lithologies is varying in the order of: RnLimestone > RnSalt> RnGypsum. The findings of the current research suggests that the study area is safe from radon related health hazards.